COMMUNICATION ERRORS IN FOOD AND BEVERAGE SERVICE: AN ANALYSIS OF WAITERS’ INTERACTIONAL COMPETENCE IN VOCATIONAL HOSPITALITY EDUCATION (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2026)
Effective communication plays a central role in determining service quality within the hospitality industry, particularly in restaurant settings where waiter–guest interaction directly shapes customer experience. This study investigates common communication errors produced by waiter students in a hospitality education program, focusing on three major dimensions: grammatical accuracy, pragmatic appropriateness, and lexical precision. Employing a qualitative descriptive design, data were collected through observation and transcription of simulated restaurant service interactions involving undergraduate hospitality students. The collected utterances were analyzed to identify recurring patterns of linguistic and pragmatic deviation. The findings reveal that grammatical errors primarily involve auxiliary omission, incorrect tense usage, and improper interrogative formation, largely influenced by first language transfer. Pragmatic errors include overly direct imperatives, insufficient mitigation strategies, and limited empathetic responses in complaint situations, indicating underdeveloped sociopragmatic competence. Lexical errors are characterized by overgeneralization, collocational inaccuracies, and limited use of hospitality-specific terminology, which affect professional credibility and persuasive effectiveness in menu explanation. The study argues that communication challenges in hospitality contexts are multidimensional and extend beyond structural inaccuracies. In restaurant service encounters, language functions not only as a medium of information exchange but also as a representation of professionalism and institutional quality. Therefore, hospitality English instruction should adopt an integrated communicative competence framework that simultaneously addresses grammatical form, pragmatic sensitivity, and lexical specialization. The findings provide pedagogical insights for vocational institutions seeking to align English language training with the communicative demands of international restaurant environments.